Effects of iron deficiency on anisotropy and ferromagnetic resonance linewidth in Bi-doped LiZn ferrite - Xiaona Jiang; Wei Wang; Zhong Yu; Ke Sun; Zhongwen Lan; Xinran Zhang; Vincent G. Harris (AIP Advances, 2017)
Bi-doped LiZn ferrites with different iron deficiencies were fabricated by a conventional ceramic method. Anisotropy constant (K1) was calculated and ferromagnetic resonance (FMR) linewidth (ΔH) was investigated. Crystalline anisotropy broadening linewidth (ΔHa) and porosity broadening linewidth (ΔHp) were derived by an approximate calculation based on dipolar narrowing theory, which play a significant role in contributions to FMR linewidth and occupy more than 90 % of ΔH. Physical and static magnetic properties of LiZn ferrite with iron deficiency are presented, which supports a decline in linewidths with increasing iron deficiency. Iron deficiency makes K1, ΔHa and ΔHp reduce. The results also show that ΔHp is the majority of contributions to ΔH in Bi-doped LiZn ferrite and densification is an effective method to decrease ΔH.